A combined scheme for maximising the output power of a Photovoltaic array under partial shading conditions. (March 2022) - Etarhouni, Mohamed; Chong, Benjamin; Zhang, Li
Highlights: MS-EC and IE algorithms have been merged to rearrange and divide 6×6 TCT PV array into sub-arrays, and then equalise the solar irradiance levels over their rows. SP-DPP converters has been utilised to perform current and voltage balancing in the array. Model-based control scheme is designed for DPP converters to achieve an accurate MPP tracking; hence, the derived model for the converters is experimentally verified. Simulation results validate the efficacy of the combined array scheme system under PSCs. The proposed scheme proves its ability to optimise the output power of the array system and shows power improvements of 11 – 48% compared to the traditional TCT structure. Abstract: The power generation performance of a solar array can be enhanced by using a scheme that combines various techniques, including Maximum Power Point Tracking (MPPT), a PV array reconfiguration, and DC-DC converters for current and voltage matching. This paper presents a novel combination of three techniques and a closed-loop control strategy to improve the performance of a large PV array initially in Tied-Cross-Ties (TCT) interconnection. Firstly a modified Magic Square-Enhanced Configuration (MS-EC) is used to permute the module positions in the array. The chosen example is a 6×6 TCT array. The resultant arrangement is then divided into four 3×3 TCT sub-arrays. Irradiance Equalisation (IE) is applied to each sub-array to make the irradiation levels match approximately between its rows. Finally, a Series-Parallel Differential Power Processing (SP-DPPs) converter scheme is applied to the four sub-arrays for maximum power point tracking. Experimental tests are presented to validate the transfer function models of these converters and the designed control scheme. The combined scheme performance is evaluated under static and dynamic shading patterns; it compares favourably with a TCT array using only bypass diodes by showing an average power gain of 11 –48% and an efficiency of 98.95% .